2004
DOI: 10.1086/424590
|View full text |Cite
|
Sign up to set email alerts
|

Some Like It Hot: The X‐Ray Emission of the Giant Star YY Mensae

Abstract: We present an analysis of the X-ray emission of the rapidly rotating giant star YY Mensae observed by Chandra HETGS and XMM-Newton. The high-resolution spectra display numerous emission lines of highly ionized species; Fe XVII to Fe XXV lines are detected, together with H-like and He-like transitions of lower Z elements. Although no obvious flare was detected, the X-ray luminosity changed by a factor of two between the XMM-Newton and Chandra observations taken 4 months apart (from log L X ≈ 32.2 to 32.5 erg s … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 108 publications
(149 reference statements)
4
31
0
Order By: Relevance
“…While the abundances determined with medium resolution spectroscopy are apparently often low, the results obtained with the global fits of high resolution data in our work or in Besselaar et al (2003) appear more reliable. We also point out that our joint fit approach, which uses a data selection comparable to Audard et al (2004), who obtained consistent results on the abundances with line-based and global models applied to high resolution X-ray spectra, results in slightly increased but still significant subsolar abundance values.…”
Section: Comparison With Other Resultssupporting
confidence: 58%
“…While the abundances determined with medium resolution spectroscopy are apparently often low, the results obtained with the global fits of high resolution data in our work or in Besselaar et al (2003) appear more reliable. We also point out that our joint fit approach, which uses a data selection comparable to Audard et al (2004), who obtained consistent results on the abundances with line-based and global models applied to high resolution X-ray spectra, results in slightly increased but still significant subsolar abundance values.…”
Section: Comparison With Other Resultssupporting
confidence: 58%
“…Various approaches have been developed (see discussion in Güdel 2004), although the basic results appear to be less dependent on the methodology than on the still significant systematic uncertainties in, and the incompleteness of, the atomic physics tabulations. In particular, Audard et al (2004) and Telleschi et al (2005) have studied several cases of coronal spectra using approaches that make use of the binned spectra, on the one hand, and of a list of extracted line fluxes on the other. In both cases, satisfactory agreement was obtained for the thermal emission measure (EM) structure and the coronal abundances.…”
Section: Multi‐temperature Fittingmentioning
confidence: 99%
“…Here we apply a multi‐temperature fit with 10 different thermal components on a grid. This method is somewhat similar to one of the approaches discussed by Telleschi et al (2005) and Audard et al (2004). For this case, the temperatures were fixed on a grid between 0.02 and 10.24 keV with a binwidth of 0.3 dex, that is, in steps of a factor of 2.0 in temperature.…”
Section: Multi‐temperature Fittingmentioning
confidence: 99%
“…Photoexcitation of the intercombination lines of He-like O by the radiation field of Algol A also failed to exhibit the phase dependence that would be expected from a compact corona. Finally, we note that Audard et al (2004) detected line broadening in excess of the instrumental profile in Chandra spectra of the active single giant YY Men (v sin i ¼ 45 km s À1 ; Piskunov et al 1990). While these authors found the measured line widths reasonably consistent with thermal broadening in the extremely hot (up to $10 8 K) corona of this star, they also suggest that some contribution from rotational broadening due to X-rayYemitting material high above the surface could be present as well.…”
Section: Coronal Structure Of Rapidly Rotating Giantsmentioning
confidence: 60%